Isolation and identification of new prenylated acetophenone derivatives from Acronychia oligophlebia. Issue 15 (3rd August 2019) - Niu, Qian-Wen; Chen, Neng-Hua; Wu, Zhong-Nan; Luo, Ding; Li, Ying-Ying; Zhang, Yu-Bo; Li, Qing-Guo; Li, Yao-Lan; Wang, Guo-Cai
Abstract: Three new prenylated acetophenone derivatives, acronyculatin P (1 ), acronyculatin Q (2 ), and acronyculatin R (3 ) were isolated from the leaves of Acronychia oligophlebia . Their structures were identified by extensive analyses of spectroscopic data (IR, UV, ESI-HRMS, 1D and 2D NMR) and comparison with the literatures. In addition, the cytotoxic activity against MCF-7 cells of the compounds were evaluated by the MTT assay and the IC50 values were 56.8, 40.4 and 69.1 μM, respectively. Graphical Abstract: